A Model for Teaching and Evaluation of Programming Courses in Online mode (Journal of Informatics Education and Research, 2024)
To protect community health in the face of the recent spread of COVID-19 epidemic, the world has shifted towards online education. Academics must handle the difficulties presented by the switch from conventional to online learning to preserve the learning process and guarantee that all learning goals are met. One of the key components of engineering education that is significantly impacted using online learning is practical experience. Due to the university's closing and the need for social distance in covid era, students were not able to access physical laboratories. In the present post-covid times, with the rising interest in online courses for skill enhancement and personal growth, institutions and ed-tech companies offering practical courses are finding it difficult to impart programming subjects to students. Another equally important aspect is the choice of right assessment technique for assessing the skill set acquired during the course. This paper proposes a model for conducting lab sessions for practical courses of computer programming, and assessment structure through which coding efficiency of a student can be judged.